A Developed Colorimetric Assay Using Unmodified Gold Nanoparticles for the Identification of Acinetobacter baumannii Isolates from Different Clinical Samples - Mohamed M. Sehree; Amani M. Al-Kaysi; Hanaa N. Abdullah (مجلة بغداد للعلوم)
Acinetobacter baumannii (A. baumannii ) is considered a critical healthcare problem for patients in intensive care units due to its high ability to be multidrug-resistant to most commercially available antibiotics. The aim of this study is to develop a colorimetric assay to quantitatively detect the target DNA of A. baumannii based on unmodified gold nanoparticles (AuNPs) from different clinical samples (burns, surgical wounds, sputum, blood and urine). A total of thirty-six A. baumannii clinical isolates were collected from five Iraqi hospitals in Erbil and Mosul provinces within the period from September 2020 to January 2021. Bacterial isolation and biochemical identification of isolates were carried out followed by DNA extraction from 36 isolates and six negative ATCC strains (Salmonalle typhi, Escherichia coli, Klebsiella pneumonia, Pseudomonas aeruginosa, Enterobacter aeruginosa, Staphylococcus aures) and only one positive control ATCC A. baumannii using Phenol/Chloroform method. AuNPs were synthesized using the citrate reduction method and examined by XDR, FTIR, UV-VIS, FE-SEM, and TEM.  The optimized colorimetric assay was employed based on unmodified spherical AuNPs and PCR amplification of 16S rRNA intergenic spacer sequences (ITS) with species-specific DNA oligo-targeters. Detection and optimization of A. baumannii amplicons using unmodified AuNPs were performed based on species-specific DNA oligonucleotide. The AuNPs assay was able to colorimetrically detect and distinguish A. baumannii from other ATCC bacterial isolates. The turnaround time of this assay was about 3 hours, including sample preparation and amplification, to show (0.025-6 ngµl-1) as a detection limit of DNA concentration. The efficacy of colorimetric detection was proved to effectively diagnose A. baumannii isolates with high sensitivity, simplicity, and robustness to rapidly diagnose A. baumannii isolates from different clinical samples.